Availability and acute risk to birds of maize, sorghum, and soybean seeds treated with neonicotinoids - Addy Orduna, Laura; Bolivar Muñoz, Paula; Camarero Abella, Pablo R.; Dardanelli, Sebastian; Canavelli, Sonia Beatriz; Mateo Soria, Rafael (Elsevier, 2025)
Research on the risk of neonicotinoid-treated seeds for birds is still scarce in South America. We addressed this issue using field data from 43 commercial fields to quantify the density of unburied seeds after sowing maize, sorghum, and soybean. Along transects with equidistant sampling points (0.25 m² metal rings), we counted unburied seeds, collected samples for residue analysis, and recorded field characteristics. We assessed bird species richness and abundance in 25 fields using 250 m strip transects. We necropsied 200 donated Eared Doves (Zenaida auriculata) to analyze diet and another 200 to detect neonicotinoid residues. Unburied seed density varied by crop (soybean>sorghum>maize) and field sector (headlands>field center) and was influenced by contour curves, soil cover, contracted sowing, seed metering, and sowing density. Richness of seed-eating birds was higher in headlands and increased with unburied seed density; abundance was highest in maize fields. Imidacloprid was detected in seeds of all three crops. Maize, sorghum, and soybean seeds were found in the doves´ gastrointestinal tract. The refined toxicity-exposure ratio (TER) was < 10 for maize and/or sorghum, indicating a high risk of acute intoxication. Our findings support re-evaluating seed treatment to reduce bird exposure to neonicotinoids and foster more sustainable farming in South America.